Posterior vs. anterior circulation infarction: demography, outcomes, and frequency of hemorrhage after thrombolysis. Issue 8 (26th August 2015) - Dorňák, Tomáš; Král, Michal; Hazlinger, Martin; Herzig, Roman; Veverka, Tomáš; Buřval, Stanislav; Šaňák, Daniel; Zapletalová, Jana; Antalíková, Kristýna; Kaňovský, Petr
Abstract : Background: Intravenous thrombolysis is considered to be the standard specific reperfusion therapy in acute ischemic stroke in both anterior and posterior cerebral circulation. Aims: Our aim was to evaluate the 90‐day outcome and rate of intracranial hemorrhage after recombinant tissue plasminogen activator administration in posterior circulation stroke and to compare the intracranial hemorrhage risk for posterior circulation stroke and anterior circulation stroke. Methods: The set consisted of 877 consecutive acute ischemic stroke patients (777 anterior circulation stroke; 100 posterior circulation stroke) who underwent intravenous thrombolysis with recombinant tissue plasminogen activator in a standard dose of 0·9 mg/kg. The role of following factors was assessed: presenting characteristics, intracranial hemorrhage classification according to ECASS I, mortality, and 90‐day clinical outcome assessed using the modified Rankin scale. Results: Good clinical outcomes (modified Rankin scale 0–2) were noted in 59% of posterior circulation stroke patients, with a mortality rate of 19%. Intracerebral hemorrhage was significantly less frequent in posterior circulation stroke than in anterior circulation stroke patients (5·1 vs. 17·2%; P  = 0·002). The risk of large hemorrhage (parenchymal hematoma 1 and 2) was 5·2 times higher in anterior circulation stroke patients ( P  = 0·007). The following additional statistically significant differences were found between posterior circulation stroke and anterior circulation stroke patients: median age, male gender, presence of atrial fibrillation, hyperlipidemia, median time to treatment, and median blood glucose level on admission. Conclusions: Our study suggests that posterior circulation stroke is associated with a lower risk of intracranial hemorrhage than anterior circulation stroke is.